Performance Analysis Of Relay Aided On Device To Device Communications Underlay 5G Cellular Network - Nur Ismy Afiah Ismy; Khoirun Ni’amah; Alfin Hikmaturokhman (Buletin Pos dan Telekomunikasi, 2023)
The increasing development of today's technology specifically in the field of telecommunications triggers new problems associated with the increasing number of network connectivity users so that this makes the increased load of traffic on the Base Station (BS). To address traffic problems, a D2D technology is needed as a solution to enhance connectivity on 5G networks. In the use of D2D is still not optimal for dealing with the rapidly increasing load of traffic due to the large number of users. This research suggests the addition of devices in D2D communication, namely Relay Node. (RN). The results of the study showed that by using the relay aided communication scheme can improve the sumrate performance parameter is 1,970 × 107 bps and the spectral efficiency is 19,704 bpz/Hz, but less effective in the power efficiency parameter is 7,672 × 103 bps/mW due to the addition of relay devices that increase power consumption. Using iterative algorithms on relay aided communication schemes has been shown to improve performance parameters values more optimally than using full duplex and half duplex communications schemes. Therefore, the relay aided scheme is the most accurate communication scheme in dealing with transmission systems on D2D because by using the aided relay scheme, sumrate and spectral efficiency are improved by 55%.